Stains against violence: Nalini Malani's strategies for durational looking. (1st April 2018) - Bal, Mieke
This article maps six strategies that Indian narrative painter Nalini Malani uses to slow down the viewing. This is the basis of the political force of her work. She relentlessly indicts political abuse, primarily violence, and uses a variety of painterly techniques to reinforce that indictment. By means of a close reading of a few paintings and a discussion of the different techniques, allusions and connections that she deploys, this article seeks to establish how painting, including abstract painting, and its techniques can be mobilized for relevance in the social-political domain.